Penggunaan Keterampilan Proses dalam Pembelajaran Fikih di SD/MI - Nasri Nasri (FONDATIA, 2021)
According to Djamarah, learning with process skills "aims to improve the ability of students to understand, realize and master a series of activities related to learning outcomes that have been achieved by students". According to Roestiyah, the purpose of the learning process is a very important component in the learning strategy; where students want to take it, what students must have, it all depends on the goals to be achieved. According to Indrawati as follows: process skills are social intellectual skills needed to be able to further develop their knowledge or concepts. With these skills, students have the opportunity to be able to acquire new concepts or information - new information. Learning and teaching are inseparable concepts. Beajar refers to what a person must do as a subject in learning. Meanwhile, teaching refers to what a teacher should do as a teacher. Two teaching and learning concepts carried out by students and teachers are integrated in one activity. Between the two, there was an interaction with the teacher. The abilities that students have from the teaching and learning process alone must be able to get results through one's creativity without the intervention of other people as teachers.